Needs Analysis for Developing Web-Based Interactive Multimedia Integrated with Spiritual Values on Chemical Equilibrium Material for Grade XI - Amaliah Shabrina; Ayi Darmana; Siti Nur Azizah (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Abstract: Needs Analysis for Developing Web-Based Interactive Multimedia Integrated with Spiritual Values on Chemical Equilibrium Material for Grade XI. This study aimed to analyze the needs for developing web-based interactive multimedia integrated with spiritual values on chemical equilibrium material for grade XI students. The study employed a research and development (R&D) method using the 4D development model limited to the define stage. The research was conducted at SMA Negeri 2 Percut Sei Tuan involving 36 students and one chemistry teacher. Data were collected through observations, interviews, and needs analysis questionnaires, then analyzed descriptively using qualitative and quantitative approaches through the stages of front-end analysis, student analysis, task analysis, concept analysis, and specifying instructional objectives. The findings revealed that students still experienced difficulties in understanding chemical equilibrium material, with a percentage of 62.96%. The need for web-based interactive multimedia reached 80.95% in the high category, while the integration of spiritual values obtained the highest percentage of 90.56% in the very high category. The results of task, concept, and instructional objective analyses indicated that the developed multimedia should facilitate cognitive and affective aspects in an integrated manner. Therefore, the development of web-based interactive multimedia integrated with spiritual values is considered capable of supporting chemistry learning that is more interactive, structured, and meaningful in accordance with students’ learning needs and the objectives of the Merdeka Curriculum.